A abordagem da dermatologia na graduação de medicina: uma reflexão sobre técnicas de ensino e core curriculum - Fischer, Nathalia Fahl Cicotti (Universidade Federal de São Carlos, 2023)
Even though skin diseases are prevalent and epidemiologically relevant, the subject of Dermatology receives insufficient attention in medicine schools, in general, and more specifically in UFSCar. Active learning methodologies are advantageous when aiming to better explore it during graduation, but students must receive a core curriculum basis
An approach of dermatology in medical school: a reflection about teaching techniques and core curriculum
Keywords: Educação médica; Dermatologia; Medical education; Dermatology; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA